Proactive Infliximab Drug Monitoring Is Superior to Conventional Management in Inflammatory Bowel Disease. Issue 2 (27th June 2019) - Fernandes, Samuel Raimundo; Bernardo, Sónia; Simões, Carolina; Gonçalves, Ana Rita; Valente, Ana; Baldaia, Cilénia; Moura Santos, Paula; Correia, Luís Araújo; Tato Marinho, Rui
Abstract : In patients with inflammatory bowel disease, proactive therapeutic drug monitoring of infliximab over a 2-year period was associated with higher rates of mucosal healing and lower surgical requirements compared with a conventional cohort treated without therapeutic drug monitoring. Abstract: Background: Increasing evidence supports the use of reactive therapeutic drug monitoring (TDM) in Crohn's disease (CD) and ulcerative colitis (UC) following secondary loss of response. It is still unknown if proactive TDM can improve clinical outcomes. Methods: Consecutive patients completing infliximab (IFX) induction therapy were prospectively allocated into a proactive TDM protocol (pTDM). Before the fourth infusion and every 2 infusions, IFX trough levels and antidrug antibodies were measured using a drug-sensitive assay (Theradiag, Lisa Tracker). Treatment was proactively escalated aiming at an IFX trough level between 3 and 7 ug/mL (CD) and 5 and 10 ug/mL (UC). A retrospective cohort treated with IFX but without TDM served as the reference group. End points included the need for surgery, hospitalization, treatment discontinuation, and mucosal healing at 2 years of follow-up. Results: Two hundred five patients were included, 56 in the proactive regimen. Treatment escalation was more common in pTDM patients (76.8% vs 25.5%; P < 0.001), who also required less surgery (8.9% vs 20.8%; P = 0.032) and presented higher rates of mucosal healing (73.2% vs 38.9%; P < 0.0001). Proactive TDM significantly decreased the odds of reaching any unfavorable outcome (odds ratio, 0.358; 95% confidence interval, 0.188–0.683; P = 0.002). Conclusions: Proactive TDM is associated with fewer surgeries and higher rates of mucosal healing than conventional non-TDM-based management.